UNRAVELING SHORT-TERM VARIATIONS IN TIDEWATER GLACIER FLOW: INSIGHTS FROM TERRESTRIAL RADAR INTERFEROMETRIC STUDIES - Cassotto, Ryan (University of New Hampshire Scholars' Repository, 2017)
Tidewater glaciers are fast-flowing valley glaciers that advect ice from the interior of ice sheets to the ocean. Processes along the submarine boundaries of tidewater glacier termini can trigger a dynamic response in glacier ice that can impact stability along the terminus. Predictions of 21st century sea level rise require a comprehensive understanding of tidewater glacier dynamics over a variety of spatial and temporal scales. Perturbations to the calving front, such as iceberg calving, tidal modulations, changes in proglacial ice mélange strength and rigidity, and the subglacial discharge of meltwater occur on time-scales that exceed temporal resolution of satellite measurements; thus, little is known about the dynamic response of glaciers to these processes. Terrestrial radar interferometry is a relatively new technology that measures millimeter scale surface deformation with a spatial resolution comparable to satellites, but at much higher temporal resolution. Here, I use terrestrial radar interferometers to measure short-term variations in speed and surface elevation along Jakobshavn Isbræ, Greenland and Columbia Glacier, Alaska. I find that small calving events can trigger large, dynamic changes in speed and ice thickness. I present observations that show that glacier response to calving events is a consequence of two competing feedbacks: (1) an increase in strain rates leads to dynamic thinning and faster flow, thereby promoting destabilization, whereas (2) an increase in flow rates advects thick ice toward the terminus and promotes restabilization. The competition between these feedbacks depends on temporal and spatial variations in the glacier’s proximity to flotation. I also present the first field evidence of a granular ice mélange influence on iceberg calving, which has implications for calving rates, the speed and thickness of the terminus, and consequently tidewater glacier stability. Finally, I present observations of a large increase in speed along Columbia Glacier in response to a ...